2014
DOI: 10.1007/978-3-319-09614-8_16
|View full text |Cite
|
Sign up to set email alerts
|

Acetaldehyde and Retinaldehyde-Metabolizing Enzymes in Colon and Pancreatic Cancers

Abstract: Colorectal (CRC) and pancreatic cancers are two very significant contributors to cancer-related deaths. Chronic alcohol consumption is an important risk factor for these cancers. Ethanol is oxidized primarily by alcohol dehydrogenases to acetaldehyde, an agent capable of initiating tumors by forming adducts with proteins and DNA. Acetaldehyde is metabolized by ALDH2, ALDH1B1 and ALDH1A1 to acetate. Retinoic acid (RA) is required for cellular differentiation and is known to arrest tumor development. RA is synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 94 publications
2
63
0
1
Order By: Relevance
“…It is well known that acetaldehyde is highly toxic and is recognized as a carcinogenic molecule to humans [117]. Moreover, acetaldehyde is considered a CRC biomarker and plays a crucial role in cancer initiation and progression [118]. Finally, relative abundance of genes of the pentose phosphate pathway was significantly higher in CRC samples.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that acetaldehyde is highly toxic and is recognized as a carcinogenic molecule to humans [117]. Moreover, acetaldehyde is considered a CRC biomarker and plays a crucial role in cancer initiation and progression [118]. Finally, relative abundance of genes of the pentose phosphate pathway was significantly higher in CRC samples.…”
Section: Discussionmentioning
confidence: 99%
“…ABCC1, ABCC3 and ABCC5 genes) are under Nrf2/ARE-mediated regulation, and increased expression of these transporters in PDAC is associated with a poor treatment response (Mohelnikova-Duchonova et al, 2013). The basal and inducible expression of several phase I and phase II drug detoxification enzymes by the Nrf2/ARE system is widely recognised, and over expression of aldo-keto reductase Li et al, 2013;Zhang et al, 2014;Yi and Oh, 2015), aldehyde dehydrogenase (Yi and Oh, 2015;Singh et al, 2015), and NQO1 (Awadallah et al, 2008) have been identified in several PDAC cell lines. Many of these drug-metabolizing enzymes as well as the antioxidant systems require NADPH as a cofactor, and Nrf2 regulates all four of the NADPH-generating enzymes.…”
Section: Cytoprotection By Are-driven Genesmentioning
confidence: 99%
“…A possible reason for this may be that ALDH2 is a major acetaldehyde-metabolizing enzyme, and its inactivation because of the Glu/Lys genotype leads to acetaldehyde accumulation, which in turn could lead to a series of symptoms that may prevent alcohol consumption (Yang et al, 2009). In addition, the potential function of the ALDH2 Glu504Lys polymorphism could be affected by gene-gene and gene-environment interactions (Singh et al, 2015). Therefore, caution should be exercised when considering this conclusion.…”
Section: Discussionmentioning
confidence: 99%